2020
DOI: 10.3390/molecules25235501
|View full text |Cite
|
Sign up to set email alerts
|

Novel Small-Molecule Scaffolds as Candidates against the SARS Coronavirus 2 Main Protease: A Fragment-Guided in Silico Approach

Abstract: The ongoing pandemic caused by the novel coronavirus has been the greatest global health crisis since the Spanish flu pandemic of 1918. Thus far, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in over 1 million deaths, and there is no cure or vaccine to date. The recently solved crystal structure of the SARS-CoV-2 main protease has been a major focus for drug-discovery efforts. Here, we present a fragment-guided approach using ZINCPharmer, where 17 active fragments known to bind to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Finally, we hope that this study opens the doors for developing metallodrugs as alternatives in the fight against SARS-CoV-2. This is a topic of current intense interest [ 66 , 67 ], and the well-established abilities of coordination complexes to inhibit different stages of the replicative cycles of several viruses may be a good starting point. Furthermore, we believe that this type of study could be useful for developing more efficient techniques for the reliable detection of SARS-CoV-2, which is also an area of intense research efforts [ [68] , [69] , [70] ], in order to control, prevent and therefore reduce its pathogenic spread.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we hope that this study opens the doors for developing metallodrugs as alternatives in the fight against SARS-CoV-2. This is a topic of current intense interest [ 66 , 67 ], and the well-established abilities of coordination complexes to inhibit different stages of the replicative cycles of several viruses may be a good starting point. Furthermore, we believe that this type of study could be useful for developing more efficient techniques for the reliable detection of SARS-CoV-2, which is also an area of intense research efforts [ [68] , [69] , [70] ], in order to control, prevent and therefore reduce its pathogenic spread.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, developing a therapy to effectively treat SARS-CoV-2 infections is still mandatory. In this context, repurposing known drugs and taking advantage of in-silico approaches are the preferred ways to promptly select clinical candidates [ 2 , 3 , 4 , 5 ] within a reasonable timeframe and at acceptable costs. Different examples are available in the literature, mainly based on the application of Virtual Screening (VS) procedures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different examples are available in the literature, mainly based on the application of Virtual Screening (VS) procedures [ 6 ]. Of note are research articles that have reported data properly validated by in-silico protocols (e.g., docking calibration) and/or in vitro assays for the identification of: (i) inhibitors of the SARS-CoV-2 main and papain-like proteases [ 3 , 4 , 7 ]; (ii) compounds targeting the receptor-binding domain (RBD) of the spike SARS-CoV-2 protein [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 has several important drug targets. These include the main protease (M pro ) [ 27 , 28 ], and the papain-like protease (PL pro ). PL pro ’s name is derived from its structural similarity to papain, an enzyme found in papaya.…”
Section: Introductionmentioning
confidence: 99%